2020
DOI: 10.31539/jpjo.v4i1.1467
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi Mahasiswa Pendidikan Olahraga terhadap Perkuliahan Daring Selama Pandemi Covid-19

Abstract: The aim of the study was to determine the perceptions of sports education students towards online lectures during the Covid-19 pandemic. The method used in this research is descriptive quantitative by examining the perceptions of students in the Sports Education Faculty of Education, University of Muhammadiyah Jakarta. Data collection techniques using surveys through online questionnaires. The number of samples used in the study amounted to 65 students. The results of this study showed the percentage of 92.3% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
(11 reference statements)
0
4
0
4
Order By: Relevance
“…In line with the results of research conducted by Komarudin and Prabowo (2020) which shows that the results of students' perceptions of online learning for physical education and health subjects are in the medium category, it can be interpreted that most students state that online learning for physical education, sports, and health is completely ineffective and not good. Furthermore, research by Yulianingsih and Parlindungan (2020) which states that the response of sports education students to online learning has been accepted because it is the only way to carry out lectures and is more effectively carried out during the Covid-19 pandemic in an effort to break the chain of spread of the Covid-19 virus.…”
Section: Outer Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the results of research conducted by Komarudin and Prabowo (2020) which shows that the results of students' perceptions of online learning for physical education and health subjects are in the medium category, it can be interpreted that most students state that online learning for physical education, sports, and health is completely ineffective and not good. Furthermore, research by Yulianingsih and Parlindungan (2020) which states that the response of sports education students to online learning has been accepted because it is the only way to carry out lectures and is more effectively carried out during the Covid-19 pandemic in an effort to break the chain of spread of the Covid-19 virus.…”
Section: Outer Receptormentioning
confidence: 99%
“…After that, Siregar (2013) who suggested that cognitive processes occur on stimuli received and interpreted by each individual. Meanwhile, research by Yulianingsih and Parlindungan (2020) reveals that perception is formed from the process of the five senses, thoughts, feelings, and memories possessed by the individual itself which will be active and interpret and then conclude, then by Martin et al (2020) perception is said to be a picture a world created by selecting, organizing, and translating information. And by Achmad (2017) perception is formed by a person's personal vision or a series of activities to provide information that can be received by one's senses regarding a phenomenon, event and so on, which is obtained through collecting information and making information conclusions and elaborating information so that someone can convey a response about the good and bad of the information.…”
Section: Introductionmentioning
confidence: 99%
“…Meskipun banyak manfaat yang telah dihasilkan dari pembelajaran online, namun hasil studi terbaru menemukan bahwa pendidikan jarak jauh berbasis online sangat membebani bagi keluarga, sekolah dan mahasiswa di semua jurusan (Brom et al, 2020). Selain itu, studi sebelumnya melaporkan bahwa pembelajaran online menunjukkan penguasaan materi pelajaran dengan kategori rendah (62%) dan banyak dari mahasiswa menyatakan merasa kesulitan untuk memahami materi pelajaran melalui online, khususnya materi-materi perkuliahan yang memiliki tingkat kesulitan yang relative tinggi (Yulianingsih & Parlindungan, 2020;Yuniarti & Hartati, 2020). Fakta selanjutnya menunjukkan bahwa pembelajaran online tidak terlalu menyenangkan dan cenderung membosankan (Komarudin & Prabowo, 2020).…”
Section: Pendahuluanunclassified
“…Jenis pendekatan dalam penelitian ini adalah deskriptif kualitatif, yaitu sebuah penelitian untuk mencoba memecahkan masalah yang dihadapi dalam kondisi saat ini. Penelitian ini nantinya berupaya untuk mengumpulkan informasi dari fenomena-fenomena yang ada secara umum kemudian diangkat menjadi sebuah permasalahan dalam penelitian dan kemudian simpulkan (Yulianingsih & Parlindungan, 2020). Sama halnya dengan pendapat (Wicaksono et al, 2020) bahwa penelitian kualitatif merupakan suatu metode penelitian yang digunakan untuk meneliti kondisi obyek yang alamiah berdasarkan fenomena yang sedang terjadi.…”
Section: Metodeunclassified
“…Pembelajaran berbasis multimedia, seperti pembelajaran lini komputer, pembelajaran lini web (e-learning), sebagai salah satu bentuk pemanfaatan TIK yang perlu diterapkan dalam dunia pendidikan saat ini (Laksana, 2020). Hal ini juga dinyatakan oleh Brown (Anugrahana, 2020) & Parlindungan, 2020). Selain itu, berbagai kampus juga memanfaatkan platform sebagai media untuk pembelajaran seperti Zoom Meeting, Whatsapp, Google Meet (Haqien & Rahman, 2020).…”
Section: A Hasil Penelitianunclassified